Research and development technique for estimating airflow and diffusion parameters in connection with the Atmospheric Water Resources Program: final report - Cermak, J. E. (Jack E.), author; Grant, Lewis O., author; Orgill, Montie M., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1969)
A stably stratified atmospheric boundary layer was simulated in a wind tunnel and utilized to determine radioactive krypton dispersion patterns over a 1:9600 scale model of the Eagle River Valley and topography surrounding Climax, Colorado. Geometric, dynamic, and thermal similarity are considered, primarily, for barostromatic airflow. Similarity criteria for transport and dispersion are considered also. This is the first time that a barostromatic airflow produced by cooling with dry ice has been documented by temperature and velocity profile measurements. Field Gata indicate that airflow and temperature characteristics over the model are approximately similar to a prototype storm. Dispersion measurements were taken by using sources representative of field ground sources. Model and field measurements confirm that seeding nuclei are reaching the target area from the present existing ground sources. Limited field measurements of ice nuclei concentrations at Chalk Mountain show a variation of 5 to 300 part./liter or XU/Q ~ 1 x 10 -9m-2 to 68 x 10-9m-2. Concentration values deduced from radioactive gas measurements over the model show values within the same range but closer to the optimum values indicated by present cloud physics models, i.e., XU/Q ~ 15 to 18 x 10-9m-2. The barostromatic airflow model indicated that topography plays an important role in determining the downwind direction of the particulate plume.
CER69-70JEC-LOG-MMO-11.
August 1969.
Period March 15, 1968 to June 30, 1969 Atmospheric Water Resources Research Bureau of Reclamation Contract No. 14-06-D-6455.
Keywords: Atmospheric diffusion; Air flow; Fluid dynamics